REMOTE WORK, ORGANIZATIONAL CULTURE, AND SOCIAL BONDS IN ABUJA ORGANIZATIONS - Sidi, Maryam Nasiru; Abdulkadir, Jaafar (African Journal of Social and Behavioural Sciences, 2025)
Remote work has evolved from a temporary solution to a permanent workplace model in many parts of the world. Initiated by the COVID-19 pandemic, it has now become a key aspect of the modern workforce, transforming not only how people perform their jobs but also how they interact with colleagues, experience company culture, and establish professional relationships. This study reviewed the relevant literature, using symbolic interactionism as the theoretical framework. The pursuit to examine how remote work has influenced organizational culture among employees in some selected organizations and the way it impact the development and maintenance of social bonds among colleagues brings about the conduct of this research. In the course of this research, a qualitative research technique was employed, utilizing in-depth interviews to gain a deeper understanding of how employees perceive changes in workplace dynamics, team cohesion, and cultural values within remote or hybrid work settings. Therefore, this research found that the transition to remote work weakened the ability to internalize institutional norms, interpret workplace values, and develop a sense of organizational identity. It further shows that remote work not only reduces the frequency of informal social interaction but also erodes the depth of relationships and emotional connection among coworkers. The study recommends that organizations encourage the development of hybrid work models that blend remote flexibility with regular in-person interactions. They should implement mentorship and onboarding programs tailored specifically for remote staff, with an emphasis on new and junior employees.